Ṭibb al-Nabawī and the Epistemological Critique of Spiritual Reduction in the Modern Biomedical Paradigm - Sulhayani Sulhayani; Sahlan Harahap; Jonson Silalahi (Kamali: Jurnal Ilmu Agama, 2026)
The dominance of the modern biomedical paradigm in contemporary health discourse is rooted in materialistic ontological assumptions and an empirical-positivistic epistemology that focuses on measurable aspects, thereby reducing the spiritual dimension to psychological variables or ignoring it. Although several studies discuss the integration of spirituality in clinical practice, there has been no comparative epistemological analysis that systematically examines the ontological foundations and methods of knowledge validation between biomedicine and ṭibb al-Nabawī. This study aims to identify the ontological and epistemological assumptions of the biomedical paradigm, analyze the knowledge framework in ṭibb al-Nabawī, and formulate a non-reductionist conceptual model of health. This study is a philosophical-conceptual research with a critical, comparative, epistemological analysis of primary and secondary texts of ṭibb al-Nabawī, as well as philosophical literature and biomedical theory, using comparative-conceptual analysis techniques to examine the relationship between ontology, epistemology, and conceptions of health. The results show that the reduction of spirituality in biomedicine is a logical consequence of the limitation of reality to physical entities and linear causal mechanisms, which has an impact on the marginalization of the dimensions of meaning, value, and transcendent relations in the construction of health. In contrast, ṭibb al-Nabawī is built on a layered ontology and an integrative epistemology that recognize revelation, reason, and experience as sources of knowledge, so that health is understood as a relational condition that coherently encompasses physical, psychological, and spiritual dimensions. Conceptually, these findings offer an alternative framework for expanding the epistemic horizon of health studies and encouraging more reflective and critical cross-paradigm dialogue.